Marital interaction, domestic violence, social support, and wives’ quality of life: a sem analysis - Mira Fauziyya Fatihanna; Diah Krisnatuti; Yulina Eva Riany (Jurnal Konseling dan Pendidikan, 2025)
Domestic violence (DV) against wives remains a serious issue in Indonesia. Marital interaction and social support play a crucial role in improving the quality of life of wives who are victims of DV. This study generally aims to examine the effects of marital interaction, domestic violence, and social support on wives’ quality of life by testing hypotheses using Structural Equation Modeling (SEM). The research employed a quantitative approach with a cross-sectional design through an online survey. The study involved 100 wives who were victims of DV, selected using purposive sampling in the Greater Jakarta (Jabodetabek) area. The instruments used included the Interpersonal Behavior Scale, Domestic Violence Frequency, Multidimensional Scale of Perceived Social Support, and a modified version of the World Health Organization Quality of Life, all of which underwent pilot testing. Data analysis was conducted using descriptive statistics and Spearman’s correlation test via SPSS. The effect testing was performed using SMART-PLS, with model fit evaluated through fit measures, yielding a GoF> 0.36, indicating acceptable model adequacy for hypothesis testing. The results showed that marital interaction had a significant negative effect on domestic violence (β = -0.752***; p < 0.001). Domestic violence had a significant negative effect on social support (β = -0.285**; p < 0.01), while social support had a significant positive effect on wives’ quality of life (β = 0.545***; p < 0.001). Interestingly, domestic violence also demonstrated a significant positive effect on wives’ quality of life (β = 0.230*; p < 0.05). In addition, marital interaction significantly and positively affected wives’ quality of life (β = 0.330**; p < 0.01). These findings indicate that all research variables are interrelated and influence wives’ quality of life, thereby supporting all proposed hypotheses. The findings of this study provide practical implications for family counseling and psychosocial interventions in the Greater Jakarta (Jabodetabek) area. Strengthening social support for wives who are victims of domestic violence is essential. Support from family members and close relatives, which remains limited, needs to be reinforced through family counseling, empathic communication training, and education on women’s rights. This study, however, has several limitations, including the absence of interviews, reliance solely on the victims’ perspectives, and data collection conducted exclusively through online surveys.